Exploring the World of Drilling (IntechOpen, 2024)
Exploring the world of oil well drilling reveals an interesting mix of technology, well completion, and engineering prowess. Drilling oil wells, a cornerstone of global energy production, involves a complex series of processes designed to extract hydrocarbons from deep within the Earth’s crust. This book provides a comprehensive overview of the current state of the art in drilling, exploring topics such as nanotechnology use in advanced oil well drilling, oil well completion strategy, drilling fluid chemistry, positive displacement motor design and performance, sonic drilling, and future drilling technology and development.